THE EFFECT OF TEACHER COMPETENCY, WORK DISCIPLINE, WORK MOTIVATION, AND PRINCIPAL LEADERSHIP ON TEACHER PERFORMANCE AT SMPN 20 KUPANG CITY, EAST NUSA TENGGARA PROVINCE, INDONESIA - Poma, Sarlianus (Universitas Riau Kepulauan, 2025)
This study aims to determine and analyze the influence of teacher competence, work discipline, work motivation, and principal leadership on the performance of teachers at SMPN 20 Kupang City, East Nusa Tenggara Province. Descriptive quantitative analysis technique. The sample used in this study was 15 respondents. Based on the data analysis, the results of the study indicated that teacher competence (X1) has a positive and significant effect on the performance of teachers at SMPN 20 Kupang City, East Nusa Tenggara Province, work discipline (X2) has a positive and significant effect on the performance of teachers at SMPN 20 Kupang City, East Nusa Tenggara Province, work motivation (X3) has a positive and significant effect on the performance of teachers at SMPN 20 Kupang City, East Nusa Tenggara Province, principal leadership (X4) does not have a positive and significant effect on the performance of teachers at SMPN 20 Kupang City, East Nusa Tenggara Province. Teacher competence (X1), work discipline (X2), work motivation (X3), and principal leadership (X4) on teacher performance (Y) simultaneously have a positive and significant effect on teacher performance at SMPN 20 Kupang City, East Nusa Tenggara Province.